NATURAL INNOVATION: How Pest Biocontrol Agents Are Redefining Modern Agriculture - Ferreira da Silva, Maria Vitória; Alessandra Carla Furlanetti (Revista Interface Tecnológica, 2025)
Contemporary agriculture faces a series of challenges, such as population growth, climate change, and the need for more sustainable production practices. In this context, pest control emerges as one of the main obstacles to efficient food production, traditionally addressed through the intensive use of chemical pesticides. However, the negative impacts of these substances on the environment and human health have driven the search for safer and more ecologically viable alternatives. Among these alternatives, biocontrol agents — living organisms such as natural predators, parasitoids, beneficial bacteria, and fungi — stand out for their ability to suppress pest populations without harming ecosystems. This article aims to analyze the applicability and benefits of using biocontrol agents in modern agriculture, highlighting their potential to promote a more balanced, sustainable, and efficient agricultural system. The use of these biological agents contributes not only to the preservation of biodiversity and the reduction of environmental contamination but also to lower production costs and decreased health risks. With technological advances, tools such as drones and monitoring systems have enhanced the effectiveness of biological control, although challenges remain, such as the need for farmer training, research investment, and adaptation to diverse agroecological conditions. Nevertheless, biocontrol agents represent a promising strategy for the future of sustainable agriculture.